Development of Science Teaching Materials Integrated Al-Qur'an Using Problem Based Learning Models - Anggi Susilawati; Meriza Faradilla; Khairul Rizal (LPPM Universitas Almuslim, 2023)
This development research aims to determine the feasibility of the steps for developing integrated science teaching materials with verses from the Qur'an using a problem based learning model. This research was conducted with expert validation, as well as teachers and students at several schools in Banda Aceh. Data collection techniques were obtained from the validation results of experts, teachers and student responses, which were obtained from a questionnaire instrument in the form of a Likert scale. Based on the results obtained, expert validation obtained an average value for the material indicator of 3.49 in the very good category, for the readability indicator an average value of 3.61 was obtained in the very good category and for the presentation indicator an average value of 3.79 was obtained. also in the very good category. Meanwhile, for teacher validation, the material indicator obtained an average value of 3.89, this means it can be categorised as very good, while for the readability indicator, an average value of 3.85 was obtained in the very good category, and for the presentation indicator, an average value of 3 was obtained. 92 is also in the very good category, and the student response value is 89.6, meaning that students have a very positive response regarding this teaching material. So this shows that the use of integrated teaching materials with Al-Qur'an verses with models is very good for use in science learning.